58 Impact of pulmonary hypertension haemodynamic presentation on clinical outcomes in patients with severe symptomatic aortic stenosis undergoing TAVI: insights from the new proposed pulmonary hypertension classification. (7th October 2015) - O'Sullivan, C; Wenaweser, P; Ceylan, O; Stortecky, S; Pilgrim, T; Meier, B; Bullesfeld, L; Windecker, S
Abstract : Background: Pulmonary hypertension (PH) frequently co-exists with severe aortic stenosis (AS) and PH severity has been shown to predict outcomes after transcatheter aortic valve implantation (TAVI). The impact of PH haemodynamic presentation on clinical outcomes after TAVI is unknown. Methods and results: Of 606 consecutive patients undergoing TAVI, 433 (71.4%) patients with severe AS and a pre-procedural right heart catheterization were assessed. Patients were dichotomized according to whether PH was present (mean pulmonary artery pressure [PAP] ≥25 mmHg) (n = 325) or not (n = 108). PH patients were further dichotomized by left-ventricular end-diastolic pressure (LVEDP) into post-capillary (LVEDP >15 mmHG; n = 269) and pre-capillary groups (LVEDP ≤15 mmHg; n = 56). Finally, post-capillary PH patients were divided into isolated (n = 220) and combined (n = 49) subgroups according to whether the diastolic pressure difference (diastolic PAP LVEDP) was normal (<7 mmHg) or elevated (≥7 mmHg). Primary-endpoint was mortality at 1-year. PH was present in 325/433 (75%) patients and was predominantly post-capillary (n = 269/325; 82%). Compared with baseline, systolic PAP immediately improved after TAVI in post-capillary combined (57.8 ± 14.1 vs 50.4 ± 17.3 mmHg, p = 0.015), but not pre-capillary (49.0 ± 12.6 vs 51.6 ± 14.3, p = 0.36) patients. As compared with no PH, a higher 1-year mortality rate was observed in both pre-capillary (hazard ratio [HR] 2.30, 95% confidence interval [CI] 1.02–5.22, p = 0.046) and combined (HR 3.15, 95% CI 1.43–6.93, p = 0.004) but not isolated PH patients (p = 0.11). Following adjustment, combined PH remained an independent predictor of 1-year mortality after TAVI (HR 3.28, p = 0.005). Conclusions: Invasive stratification of PH according to haemodynamic presentation predicts acute response to treatment and 1-year mortality after TAVI.